Voices and instruments of the middle ages: instrumental practice and songs in France 1100-1300 - Page, Christopher 1952- (London J. M. Dent & Sons LTD, 1987)
If you are interested in performing troubadour and trouvere music as authentically as possible and haven't yet read this book, run and get yourself a copy. Page's research was probably the impetus for moving away from the "big band" approach of the '60s and '70s, and also helped to free up rhythmic possibilities in the genre. Still relevant, and readable.
Keywords: Middle Ages (500-1400); Music history; Song; Instrumentation; Troubadour; Accompaniment; Performance; France